Schlussbericht zum Vorhaben "Additive Leichtbaustrukturen für Flugzeugkomponenten" : Verbund: KOBFS - Kostenoptimierter Baukasten für Flügelsysteme - Ahlers, Dominik; Tröster, Thomas

Nationale Forschungsdateninfrastruktur, die Initiative NFDI4Culture und die Musikwissenschaft - Pasdzierny, Matthias; Röwenstrunk, Daniel; Schmidt, Dörte (Die Musikforschung)

Fokusthemen und Aufgabenbereiche für eine Forschungsdateninfrastruktur zu materiellen und immateriellen Kulturgütern. Living Document der NFDI-Initiative NFDI4Culture. - Altenhöner, Reinhard; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Blümel, Ina; Bulle, Klaus; Effinger, Maria; Hammes, Andrea; Hartmann, Thomas; Kailus, Angela; Kett, Jürgen; Pittroff, Sarah; et al.

Method of superposing a multiple driven magnetic field to minimize stray fields around the receiver for inductive wireless power transmission - Lange, Sven; Büker, Maik-Julian; Sievers, Denis; Hedayat, Christian; Förstner, Jens; Hilleringmann, Ulrich; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)
This paper presents a new methodology by using a multiple coil array for energy transmission. The complex current strengths of the transmitting coil array are calculated by having the knowledge about of the mutual inductances and the symmetries of the transmitting coil array, so that its resulting magnetic field mainly penetrates only the receiving coil and is strongly attenuated outside. This method is used for an optimized wireless energy transmission but can also be implemented for other inductive applications.

Inductive Locating Method to Locate Miniaturized Wireless Sensors within Inhomogeneous Dielectrics - Lange, Sven; Schröder, Dominik; Hedayat, Christian; Otto, Thomas; Hilleringmann, Ulrich (2019 17th IEEE International New Circuits and Systems Conference (NEWCAS))
For the measurement of process data in bioreactors, very small wireless sensors are currently under development to replace the conventional rod probes. The so-called Sens-o-Spheres measure the temperature and in future the oxygen content and the pH of fluids. In order to evaluate the distribution of the measured values within the process, it is necessary to locate the wireless sensors. Because of the small size of the sphere (diameter 8 mm), inhomogeneous ambient media and the size of the reactor (less than 2 m), an inductive locating by magnetic fields with a frequency of f = 13.56 MHz is necessary. Since the behaviour of the magnetic field is very different from that of the electromagnetic wave, new locating methods are required, which are presented in this paper.
Keywords: oxygen content; inhomogeneous ambient media; magnetic field; inductive locating method; miniaturized wireless sensors; inhomogeneous dielectrics; conventional rod probes; Sens-o-Spheres measure; frequency 13.56 MHz

Success Factors for the Consolidation and Anchoring of Digitalisation Projects - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Hochschulforum Digitalisierung (2019). Strategies Beyond Borders – Transforming Higher Education in a Digital Age. Book of Abstracts)

Digitalisierungsstrategien auf dem Prüfstand – eine empirische Untersuchung auf Basis der Grounded-Theory-Methodologie an deutschen Hochschulen - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Teilhabe an Bildung und Wissenschaft)

Stellungnahme der DFG-Kommission zur Evaluierung des Förderprogramms „Fachinformationsdienste für die Wissenschaft“ - Oevel, Gudrun

Grammatikwandel digital-kulturwissenschaftlich erforscht. Mittelniederdeutscher Sprachausbau im interdisziplinären Zugriff - Merten, Marie-Luis; Seemann, Nina; Wever, Marcel Dominik (Niederdeutsches Jahrbuch)

Digitaler Wandel als strategischer Transformationsprozess – zum allgemeinen und hochschulspezifischen Verständnis der Digitalisierung - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie

Influence of the free-electron concentration on the optical properties of zincblende GaN up to 1×1020cm−3 - Baron, Elias; Goldhahn, Rüdiger; Deppe, Michael; As, Donat Josef; Feneberg, Martin (Physical Review Materials)

Adhesive bonding of FDM-manufactured parts made of ULTEM 9085 considering surface treatment, surface structure, and joint design - Bürenhaus, Franziska Isabelle; Moritzer, Elmar; Hirsch, André (Welding in the World)

Advancing into New Dimensions - Moritzer, Elmar; Bürenhaus, Franziska Isabelle; Hirsch, André (Kunststoffe internationl)

Vorstoß in neue Dimensionen - Moritzer, Elmar; Bürenhaus, Franziska Isabelle; Hirsch, André (Kunststoffe)

Einfluss des Werkzeugdesignes auf das Erwärmverhalten beim Warmgasschweißen - Albrecht, Mirko; Gehde, Michael; Bialaschik, Max; Schöppner, Volker

A KPI-based Condition Monitoring System for the Beer Brewing Process - Pasic, Faruk; Wohlers, Benedict; Dziwok, Stefan; Becker, Matthias; Heinrich, Matthias (2019 24th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

AuthCheck: Program-state Analysis for Access-control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (10th Workshop on Tools for Automatic Program Analysis (TAPAS))

Coaching on the Job bei Unternehmen des Maschinen- und Anlagenbaus - Wissenslücken schließen zur Weiterpflege modernisierter IT-Anwendungen - Fazal-Baqaie, Masud; Strüwer, Jan-Niclas; Schmelter, David; Dziwok, Stefan (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Improvement of Software Requirements Quality based on Systems Engineering - Holtmann, Jörg

Component-Based Refinement and Verification of Information-Flow Security Policies for Cyber-Physical Microservice Architectures - Gerking, Christopher; Schubert, David (International Conference on Software Architecture (ICSA 2019))